The Vegetation of Coimbatore District - Shankarnarayan, K. A.; Gupta, R. K. (Indian Forester, 1959)
The physical position, configuration of the ground and climate of Coimbatore district are presented. For convenience of description the forest of both Coimbatore North and South are dealt with separately. In the former two types of vegetation are there namely (1) The Southern Tropical Thorn Forest and (2) Southern Tropical Dry Deciduous forest according to champion's classification. While in the latter five types of forests are met with viz. (1) Southern Wet Temperate, (2) Southern Tropical Wet Evergreen, (3) Southern Tropical Moist Deciduous, (4) Southern Tropical Dry Deciduous and (5) Southern Tropical Thorn Forests. The Southern thorn forest generally consists of Acacia latronum as dominant. Anogeissus latifolia is predominant in the Dry deciduous type. In the Moist deciduous forest, Tectona grandis is dominant associated with Terminalia tomentosa. The wet Evergreen forest has mainly species like Hopea parviflora, Mesuaferrea, Calophyllum elatum, etc. Syzygium calophyllifolium, S. arnottianum and Meliosma wightii dominate the Southern wet Temperate forest. Grasslands here are regarded as "Subclimax" principally consisting of Themeda cymbaria and Cymbopogon polyneuros, etc.